The Austrian HOV-lane – experiences in implementation and operation - Berger, Wolfgang J. (Journal of Civil Engineering and Management, 2002)
The ever increasing use of private vehicles for daily commuting trips contributes to a rising level of congestion in metropolitan areas. The trip times for each driver grow constantly. Just this situation is approaching Linz (ca 200 000 inhabitants), which is the capital of Upper Austria and also the political and economical centre of the region. At one every workday morning heavily congested arterial road towards the city, since 1998 high occupancy vehicles (HOV) with 3 or more occupants (3+) have been permitted to use the existing bus lane too. The opportunity to save time should encourage commuters to share their cars and should result in a more efficient car use. Based on a study, by which the efficiency of that first HOV-lane in Austria was investigated, the effects and the influences on the trip duration, commuting behaviour, drivers attitudes towards the measure, bus drivers' and policemen's experiences as well as the environmental and public costs are described. Additionally, some imperfections are revealed concerning, for instance, the used traffic signs. As the main outcome the implementation of this HOV-lane proves to be a practical approach for improving the bad commuting traffic situation on a local level. However, it must be seen only as one of many measures that would be necessary to create a real sustainable solution for the whole metropolitan area.Frist Published Online: 30 Jul 2012